Attitudes of teachers towards teaching in values to students of elementary school - Sotil Brioso, Amparo (2005)
OBJETIVE: Study such as the attitudes towards the educational ones opposite to teaching in values of him are students of primary in the files metropolitan. DESIGN: Descriptive comparative. INSTRUMENTS AND METHODS: Probabilistic sampling by conglomerates; the sample give birth the study was adjusted by 800 primary level of Lima metropolitan teachers. One a stopover of attitudes towards the educational ones built to teaching in values and a personal datum card applied one. The statistical analysis instrument psychometric to build the attitude stopover and evaluate it validity and confiability was developed in three stages; descriptive of the studied variables, and the comparisons according to the changeable independent assignees. RESULTS: Psychometric analyses indicated that mounth group presented 2 factors, results indicated that the stopover had validity and confiability observed one that them marks of the participants in the factors and the attitude stopover total presented similar values to the normal distribution. One also observed that significant statistical differences in the grade in which the kind of management of the school where he works the educational one, the educational education of origin nor by sex centre are one showing, do not exist. CONCLUSIONS: The stopover of attitudes towards the educational ones opposite to teaching in values presents validity and confiability, the educational ones, present positive attitude levels and do not exist you differentiate in the comparisons according to the studied variables.